Questioning Halal tourism motive: In between da’wa, business, and life story - Purwandani, Intan (Taylor and Francis, 2022)
This chapter demonstrates Muslim tourist operators’ motivations for providing Halal services and amenities. They describe the word da’wa, which they thought meant something other than profit-seeking in the tourism sector. The narrative method addresses the topic of how and why da’wa manifests itself in the business of Muslim tourism operators, taking into account their life story as a minority. The findings reveal three major aspects of da’wa perception and practice in the tourist industry. First, da’wa in business is viewed as an obligation to teach non-Muslims by displaying understanding of what Muslims require. Second, da’wa is shown by giving charity/sadaqah to everyone in order to devote a true example of Islamic ethical system (justice/adalah) while initiating a dialogue in order to integrate into non-Muslim culture in particular. Third, da’wa refers to the building of bonds between Muslim tourism businesses, Muslim visitors, and Muslim staff. Because da’wa is about spiritual motivation, practicing da’wa in the framework of the interplay between religion and commerce in the tourist sector in this study takes into account the sociological and historical background of a location as well as the individual life narrative. Because da’wa may be seen in every single thing a Muslim does.